Relasi Budaya dan Kuasa dalam Konstruksi Islam Kultural Pasca-Reformasi - Huda, M. Qomarul (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This article will examine the cultural construction of the post-reform Islam has offered a variety of opportunities and challenges. Through content analysis and social hermeneutics (which is defined as a personal interpretation of the human as a social action, this study detects that the construction of the Islamic cultural post-reform is a form of political responses Islamic culture. Through cultural ideology, politicians take advantage of the cultural basis for the crawl political interests at the same time releasing its cultural organizations from the burden of political stigmatization that could happen someday. kulturalisasi Also the political process that the political process without developing Islamic symbols. bid with culture-based politics is beneficial but at the same harm on the other.